Pengendalian Kualitas Produk Griller Menggunakan Failure Mode Effect and Analysis (FMEA) dan Root Cause Analysis (RCA) - Chusnah, Asma’ul; Cahyana, Atikha Sidhi (Universitas Teuku Umar, 2024)
A company engaged in the slaughterhouse of boiler chickens and one of its products is griller, which is chicken that is cut in a halal manner and packaged in the form of a whole carcass. Based on daily reports, the number of defects found in griller products shows a percentage of up to 30%. The purpose of this study is to identify the types of defects found in grillers so that alternative improvements can be determined. This research uses the Failure Mode Effect Analysis (FMEA) method to identify the most dominant types of defects in the product and find the causes. The highest defects from the FMEA results are processed by the Root Cause Analysis (RCA) method to provide improvement proposals so as to reduce the number of existing defects. The results of this study show that the most dominant type of defect is feathers remaining on the carcass with the highest RPN value of 175. The defect of feathers still remaining on the carcass is caused by workers who do not follow the SOP correctly, the changing size of raw materials, and rubber. The plucking machine is worn and loose, the settings of the plucking machine are loose, the temperature of the scalder tends to drop, the inspection in the process is not correct, there is no information on how to operate the machine, the raw materials are not uniform, and the working environment temperature is high and noisy.